Phosphorus removal from secondary wastewater effluent using copper smelter slag - Moatlhodi Wise Letshwenyo; Thandie Veronicah Sima (Heliyon, 2020)
This study investigated the use of copper smelter slag for the removal of phosphorus from secondary wastewater effluent through batch tests. The media was physically and chemically characterized and showed presence of Fe2O3 (45.22%), SiO2 (14.98%), Al2O3 (3.21%), CaO (1.99%), SO3 (1.77%) and MgO (1.33%). Scanning electron microscopy monographs revealed smooth and flat surface and no heterogeneity on the surface of the slag with visible micro pores before the experiment and less visible after the experiment. The point of zero charge of the media was 5.0. Equilibrium was reached after 4 h at 29.5 ± 0.71% phosphorus removal efficiency and media dosage of 0.4/100 mL. The kinetic data was best described by Pseudo second order equation. More than one mechanisms were involved in the adsorption of phosphorus onto copper smelter slag as suggested by multi-linearity of intra particle diffusion model. Ninety seven percent (97.5 ± 0.0%) removal efficiency was achieved at an equilibrium dosage of 160 gL-1. The equilibrium isotherm was described better by Langmuir equation with observed maximum adsorption capacity of 0.16 mg P g−1 media and the experimental maximum adsorption capacity was 0.26 mg P g−1 media. Regeneration studies showed low performance with maximum efficiency of 11.7% revealed during the first regeneration trial therefore low practical benefits. Copper smelter slag is a poor adsorbent for phosphorus and further studies on the media should be conducted.